Thermoelectric Performance Enhanced by Destructive Quantum Interference in Nanoporous Carbon Nanotube Based Junctions. Issue 11 (21st September 2021) - Wang, Jue; Wu, Dan; Huang, Lin; Cao, Xuan-Hao; Ding, Zhong-Ke; Zeng, Yu-Jia; Luo, Nan-Nan; Tang, Li-Ming; Chen, Ke-Qiu
Abstract : Aided by density functional theory with nonequilibrium Green's functions simulations, the thermoelectric (TE) properties of nanoporous carbon nanotube junctions formed by covalently binding carbon nanotubes via benzene bridges with either meta‐ or para‐connections are investigated. The results show that the TE performances of meta‐connected nanoporous carbon nanotube junctions are significantly improved due to the influence of destructive quantum interference (DQI) effect. Moreover, the TE properties of meta‐connected carbon nanotube junctions can be further improved by substitution of nitrogen atom and gate voltage. The reason is that the quantum interference patterns can be transformed from DQI to constructive quantum interference (or Fano resonance). The theoretical analysis shows that the TE figure of merit (ZT) for meta‐connected carbon nanotube junctions at room temperature is close to 0.5 near the Fermi level, ≈20 times higher than that of the perfect carbon nanotube junction. These results reveal that quantum interference effect can indeed be used to enhance the TE performance of molecular junctions. Abstract : The quantum interference effect is confirmed to be an effective strategy to achieve highly efficient thermoelectric power conversion at room temperature. Furthermore, the maximum of ZT of the nanoporous carbon nanotube junction with meta‐connections is close to 0.5 by nitrogen atom doping and gate voltage, ≈20 times larger than that of the perfect CNT junction.